2012
DOI: 10.1088/2041-8205/754/1/l8
|View full text |Cite
|
Sign up to set email alerts
|

C, N, and O Isotopic Heterogeneities in Low-Density Supernova Graphite Grains From Orgueil

Abstract: We report on the results of NanoSIMS isotope imaging of low-density supernova graphite grains from the Orgueil meteorite. 70nm-thick microtomed sections of three supernova graphite grains were deposited on Si wafers and isotopically imaged in the NanoSIMS. These sections contain hotspots of excesses in 18 O and 15 N, which are spatially well-correlated, and are likely carried by internal TiC subgrains. These hotspots are considerably more enriched in 18 O and 15 N than the host graphite grain. Correlations bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…Isochrons reported in this paper were derived from more than 450 depth profiles of samples whose data were published in previous studies, including presolar graphite grains from the Orgueil (CI1; Jadhav et al 2006;Groopman et al 2012;Jadhav et al 2013; (Nittler et al 2008) grains, whose major elements include Al, were also analyzed in this study (see Section 3.3).…”
Section: Samples and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isochrons reported in this paper were derived from more than 450 depth profiles of samples whose data were published in previous studies, including presolar graphite grains from the Orgueil (CI1; Jadhav et al 2006;Groopman et al 2012;Jadhav et al 2013; (Nittler et al 2008) grains, whose major elements include Al, were also analyzed in this study (see Section 3.3).…”
Section: Samples and Experimental Methodsmentioning
confidence: 99%
“…Recent isotopic, microstructural, and theoretical studies (Groopman et al 2012(Groopman et al , 2014Jadhav et al 2013;Pignatari et al 2013;Amari et al 2014) have concluded that the He/C and He/N SN zones (named for the most abundant chemical species, Meyer et al 1995) are the most likely dominant sources of material that condensed to form presolar SN graphite and SiC grains, with small contributions from the much deeper Si/S zone. The He/N zone, which has experienced complete H burning, was previously assumed to be the source of high inferred initial Al Al (Figure 16), confirming the findings of previous studies (e.g., Lin et al 2010;Jadhav et al 2013).…”
Section: Supernova Modelsmentioning
confidence: 99%
“…In order to account for 18 O excesses and high-inferred 26 Al/ 27 Al ratios, Clayton proposes that carbonaceous grains collect material from the He/C and He/N zones when they traverse material from these zones. However, the finding of correlated large 15 N and 18 O excesses in the interior of LD graphite grains (Groopman et al, 2012) shows that the Clayton model cannot be correct.…”
Section: Type X Grainsmentioning
confidence: 98%
“…The chosen beam energy allows to fullfill the prescriptions for the validity of the Impulse Approximation: (a) the wavelength associated to the entry channel is smaller than the nuclear radius of deuteron(λ=1.54 fm), in order to maximize the probability that quasifree reaction mechanism occurs; (b) the incident center-of-mass energy is higher than the binding energy of deuteron (E cm =4.82 MeV). Several kinematical constraints are used in order to select events corresponding to different possible reactions on deuterium having three body in the final state, namely 2 fig. 1 (left panel) and it is in agreement with the theoretical value shown by the arrow.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Neutron-capture reactions on 18 F play an important role in the explosive production of 15 N. Presolar meteoritic low-density graphite grains from supernovae show spatially correlated excess in 15 N and 18 O, which mostly come from the helium rich layers of supernova [1,2]. In particular the 15 N abundance shows a strong peak in the inner part of the helium shell due to explosive stellar nucleosynthesis [3].…”
Section: Introductionmentioning
confidence: 99%